2011
DOI: 10.1039/c1cc00020a
|View full text |Cite
|
Sign up to set email alerts
|

Benzothiazole-substituted benzofuroquinolinium dye: a selective switch-on fluorescent probe for G-quadruplex

Abstract: A new switch-on fluorescent probe containing the natural product cryptolepine analogue benzofuroquinolinium moiety (binding scaffold) and a benzothiazole moiety (signalling unit) shows a remarkable fluorescence enhancement selective for the G-quadruplex nucleic acid structure. Binding studies revealed that the highly selective response of the fluorescent probe arises from end-stack binding to G-quadruplex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 31 publications
(9 reference statements)
1
40
0
Order By: Relevance
“…E. coli BL21(DE3) cells were transformed with the pRSET-A-S vector carrying S. aureus FtsZ with a 6-histidine tag attached at its N-terminus under the control of a T7 promoter [37]. The transformed E. coli strain was streaked on a nutrient agar plate containing 50 µg/mL ampicillin, and the agar plate was incubated at 37°C overnight.…”
Section: Methodsmentioning
confidence: 99%
“…E. coli BL21(DE3) cells were transformed with the pRSET-A-S vector carrying S. aureus FtsZ with a 6-histidine tag attached at its N-terminus under the control of a T7 promoter [37]. The transformed E. coli strain was streaked on a nutrient agar plate containing 50 µg/mL ampicillin, and the agar plate was incubated at 37°C overnight.…”
Section: Methodsmentioning
confidence: 99%
“…By following a similar strategy, Wong and co-workers fused a natural product benzofuroquinolinium moiety with Thiazole Orange to give a benzofuroquinolonium-benzathiazole hybrid (30). [203] This compound also exhibited very impressive G-quadruplex selectivity and fluorescence enhancement compared to duplex DNA. When applied to fixed cells, it showed intense staining of nucleoli.…”
Section: Classic Groove Bindersmentioning
confidence: 99%
“…[13] Recently, a chemosensor has been presented that enables the fluorimetric differentiation of quadruplex DNA from other nucleic acids in cells. [14] Moreover, it has been shown that the fluorimetric discrimination of regions with different polarities may be accomplished in cells with quinoxaline derivatives. [15] Along these lines, the use of near-infrared (NIR, 650-900 nm) fluorescent probes is advantageous for biological applications, because NIR fluorophores exhibit low or almost no phototoxicity, relatively deep penetration into tissue, and negligible interference with the autofluorescence of cells.…”
mentioning
confidence: 99%